COVID-19: The need for an Australian economic pandemic response plan. Issue 4 (December 2020) - Higginson, Shannen; Milovanovic, Katarina; Gillespie, James; Matthews, Andrew; Williams, Christopher; Wall, Laura; Moy, Naomi; Hinwood, Madeline; Melia, Adrian; Paolucci, Francesco
Highlights: Australian government COVID-19 pandemic policy response impacts GDP, unemployment. Government policymaker guide for holistic, robust solutions to health emergencies. Australian Economic Pandemic Response Plan: effective fiscal and monetary policy. Healthcare system demand and supply shocks PPE, ICU bed capacity, surgery, PHI. Epidemiological and econometric modelling, disease transmission and risky behavior. Abstract: Objectives: Pandemics pressure national governments to respond swiftly. Mitigation efforts created an imbalance between population health, capacity of the healthcare system and economic prosperity. Each pandemic arising from a new virus is unknown territory for policy makers, and there is considerable uncertainty of the appropriateness of responses and outcomes. Methods: A qualitative approach was used to review mixed sources of data including Australian reports, official government publications, and COVID-19 data to discern robust future responses. Publicly available epidemiological and economic data were utilised to provide insight into the impact of the pandemic on Australia's healthcare system and economy. Results: Policies implemented by the Australian Government to mitigate the spread of COVID-19 impacted the healthcare sector and economy. This paper incorporates lessons learned to inform optimal economic preparedness. The rationale for an economic response plan concomitant with the health pandemic plan is explored to guide Australian Government policy makers in ensuring holistic and robust solutions for future pandemics. Conclusions: In future, an Australian Economic Pandemic Response Plan will aid in health and economic system preparedness, whilst a strong Australian economy and strategic planning will ensure resilience to future pandemics.